3D Structures: Inverse Opal Scaffolds with an Embossed Surface Pattern Prepared from Sticky Golf‐Ball‐Shaped Microparticle Assemblies (Adv. Mater. Interfaces 12/2015). Issue 12 (19th August 2015) - Kim, Sang Woo; Lee, Kwan‐Woo; Yi, Sang‐A; Cho, Kuk Young
<x xml:space="preserve">Abstract</x> An emboss‐patterned inverse opal scaffold is fabricated using an opal structure from uniform‐sized golf‐ball‐shaped microparticles, as described by K. Y. Cho and co‐workers in article 1500152. The optimized stickiness of the microparticles can be obtained by the compositional control of the biodegradable copolymers used and leads to stable bridging among the particles while preventing surface patterns from collapsing. This approach provides combined advantages of patterned surfaces and sophisticated three dimensional porous structures for biomedical applications.